Data Protection - Perú - Reátegui Valdiviezo, Maritza (Revista de Derecho, 2019)
The present article refers to the implementation of the Protection of Testing Data for pharmaceutical products in the light of the implementation of the FTA signed by Peru and the United States of America and the application of the definitions given by the TRIPS for this figure. The national legislation and the applicable treaties are analyzed as well as the first cases of protection to the new chemical entities given by the regulatory authority. The successes and drawbacks of the new Testing Data legislation. Their impact on heath and research issues.